Parental experiences of education at home during a pandemic - Sanna Rehman; Katherine Gibson Smith; Amudha Poobalan (University of Aberdeen, School of Education, 2021)
This study aimed to explore parental experiences of home education including the advantages, challenges and coping strategies utilised. An online cross-sectional questionnaire survey was conducted which included: demographic questions, the Perceived Stress Inventory, and open-ended questions. Participants (n = 152) were recruited from support groups and social networks. The majority of the participants were female (81.6%), working full time (40.8%), married (79%) and had been home educating since COVID-19 school closures (79.6%). The mean perceived stress score among participants was 20.6 (SD = 9.7) which represented a moderate level of stress. The results of this study showed significantly higher levels of perceived stress for parents who had been home educating due to COVID-19 school closures compared to parents who had been electively home educating. Parents who had been electively home educating for less than six months experienced significantly higher levels of stress compared to parents who had been electively home educating for more than six months. Analysis of marital status showed that single parents experienced significantly higher levels of stress compared to those living with their partner. Qualitative analysis identified three themes underpinning the home education experience: positivity in home education; challenges and demands; coping methods. This study provided insight into parental experiences throughout an unprecedented time within society and highlighted the ways in which families with school-aged children were impacted throughout a pandemic environment. The outcomes provide indicators which may be used in developing appropriate interventions to support home educators.